AN ANALYSIS OF STUDENTS’ MOTIVATION IN STUDYING ENGLISH AT SMPN 7 TARAKAN - Uka, Sarti; Rafiqa, Syarifa; Winiyanti, Rita (Universitas Borneo Tarakan, 2022)
Motivation is one of the most influential factors in achieving a target language. The purpose of this research was to determine the level of motivation in studying English at SMPN 7 Tarakan, to assess if the students had intrinsic or extrinsic motivation. This research was a descriptive research method and the population for this research was the eighth grade of SMPN 7 Tarakan with class VIII-1 was selected as a sample from random sampling technique. Furthermore, the data was collected using a questionnaire instrument consisting of 20 questions. The result of this research shows that the total mean score of extrinsic motivation is higher than the total mean score of intrinsic motivation (3,583,85). It means that class VIII-1 as a sample had higher extrinsic motivation than intrinsic motivation in studying English. In other words, students are well motivated by extrinsic motivation, but also intrinsic motivation is still at a moderate level.Â